Application of transfer functions to the thermal processing of sweet and sour cherries preserves: Influence of particle and container sizes - Márquez, C.A. (2003)
The conditions of thermal processing of fruit preserves packed in transparent glass containers have great importance from the point of view of the final product appearance. Process simulation can allow to predict the quality of the product and its possible degradation. This work applied the transfer function method to simulate the pasteurisation of whole sweet and sour cherries canned in glass containers, with a 25 °Brix sucrose solution as covering liquid, and the predicted results were experimentally tested. The influence of fruit and container diameters on the treatment times was analysed. Kinetic models for enzyme degradation were coupled to the prediction model as examples of the possibilities of optimising the whole pasteurisation process. The accuracy (average error in predicted temperatures: 2.1%) of the simulation method was satisfactory for practical purposes, its use resulted simple and fast, and it allowed adjusting of pasteurisation times, even during the process.